The Role of Folic Acid Supplementation in Reducing Anemia Complications in Patients with Chronic Kidney Disease: A Systematic Analysis of Randomized Controlled Trials - I Made Eryana; I Gede Risnawan Suastika Ardanayasa (Greenation Publisher & Yayasan Global Research National, 2025)
Chronic Kidney Disease (CKD) is a global health issue with an increasing prevalence, particularly among the elderly population. One of the major complications of CKD is anemia, which negatively impacts patient outcomes, leading to reduced quality of life and increased morbidity and mortality. Folic acid supplementation has been proposed as an effective intervention for managing anemia in CKD patients, but its clinical impact remains controversial. This systematic review aims to evaluate the role of folic acid supplementation in reducing anemia-related complications in CKD patients. Methods: A systematic search was conducted using PubMed, Science Direct, Google Scholar, and the Cochrane Library for randomized controlled trials (RCTs) published between 2014 and 2024. Included studies were those assessing the effects of folic acid supplementation on anemia in CKD patients. The Cochrane Risk of Bias Tool was used to assess the quality of the studies. Data on hemoglobin levels, erythropoiesis-stimulating agent (ESA) use, and other anemia-related outcomes were extracted and synthesized narratively. Results: Five RCTs involving 681 patients were included. Folic acid supplementation consistently improved hemoglobin levels and sideremia in CKD patients across all studies. Three studies reported significant reductions in inflammation markers. One study demonstrated a protective effect of folic acid against contrast-induced nephropathy. Adverse events were rare, with only one study reporting a slight increase in uric acid levels in some patients. Discussion: Folic acid supplementation appears to be an effective and safe intervention for improving anemia in CKD patients, particularly in those with resistance to conventional iron therapies. The benefits include improved hemoglobin levels, reduced inflammation, and potential protection against nephropathy. However, further long-term studies are needed to evaluate the stability of these effects and their impact on patient outcomes.